Identity and sociology in the Middle East - Hossein Rawande, Seyed Hossein Sadeghi (Opción, 2019)
In this study, we are looking at a structuralists’ view of discerning identity in the Middle East with regard to theoretical methodologies such as the analysis of literature. Ibn Khaldun believes the historical sociology as the science of the transformations of society. He considered all the elements of society, including social groups, science and philosophy, arts and literature, education, society, mythology, mysticism, medicine, pharmacy, etc., in the compilation of the books of the sociology of history. Hundreds of years before the sociologists of the twentieth century, Ibn Khaldun concluded that the history of sociology must necessarily be descriptive and analytic.